Keragaan Karakter Morfologi dan Agronomi Galur-Galur Sorgum pada Dua Lingkungan Berbeda - Saniaty, Arina; ,, Trikoesoemaningtyas; Wirnas, dan Desta (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTThe phenotype is a result of expression from genetic, environment, and their interaction. Genetic X environment interaction information is important for plant breeders to determine stable genotypes in various environments or stable genotypes in specific environments. The objective of this study was to evaluate morphological and agronomical traits and genetic X environment interaction of IPB sorghum breeding lines. The characterization was conducted at IPB experimental Field, based International Union for The Protection of New Varieties of Plants (UPOV), used 16 IPB sorghum breeding lines and six national varieties. Evaluation of genetic Х environment interaction was conducted in Gowa South Sulawesi and Bogor West Java. This experiment used 16 sorghum lines and two national varieties. The results showed that breeding lines exhibited variation in morphological traits, have medium plant height, small diameter, short panicle length, and medium 1,000 grain weight. There was qualitative genetic X environment interaction on panicle length, days to flowering, 1,000 grain weight, grain filling rate, grain yield, and productivity. UP/N-124-7, UP/N-89-3, UP/N-151-3, UP/N-32-8, UP/N-17-10, UP/N-4-3, UP/N-118-3, and UP/N-118-7 were well adapted in dry soil with dry climate. UP/N-48-2, UP/N-32-8, UP/N-17-10, UP/N-156-8, UP/N-118-3, and UP/N-139-1 were well adapted in dry soil with wet climate.Keywords: characterization, IPB sorgum breeding lines, qualitative genetic X environment interaction